Chitosan solution enhances the immunoadjuvant properties of GM-CSF - Zaharoff, David A. (2007)
Sustained, local delivery of immunomodulatory cytokines is under investigation for its ability to enhance vaccine and anti-tumor responses both clinically and preclinically. This study evaluates the ability of chitosan, a biocompatible polysaccharide, to (1) control the dissemination of a cytokine, GM-CSF, and (2) enhance the immunoadjuvant properties of GM-CSF. While cytokines have previously been delivered in lipid-based adjuvants and other vehicles, these do not have the clinical safety profile or unique properties of chitosan. We found that chitosan solution maintained a measurable depot of recombinant GM-CSF (rGM-CSF) at a subcutaneous injection site for up to 9 days. In contrast, when delivered in a saline vehicle, rGM-CSF was undetectable in 12 to 24 hours. Furthermore, a single s.c. injection of 20μg rGM-CSF in chitosan solution (chitosan/rGM-CSF(20μg)) transiently expanded lymph nodes up to 4.6-fold and increased the number of MHC class II expressing cells and dendritic cells by 7.4-fold and 6.8-fold, respectively. These increases were significantly greater than those measured when rGM-CSF was administered in saline at the standard preclinical dose and schedule, i.e. 4 daily s.c. injections of 20μg. Furthermore, lymph node cells from mice injected with chitosan/rGM-CSF(20μg) induced greater allogeneic T cell proliferation, indicating enhanced antigen presenting capability, than lymph node cells from mice injected with rGM-CSF alone. Finally, in vaccination experiments, chitosan/rGM-CSF was superior to either chitosan or rGM-CSF alone in enhancing the induction of antigen-specific CD4(+) proliferation, peptide-specific CD8(+) pentamer staining and cytotoxic T cell lysis. Altogether, chitosan/rGM-CSF outperformed standard rGM-CSF administrations in dendritic cell recruitment, antigen presentation and vaccine enhancement. We conclude that chitosan solution is a promising delivery platform for the sustained, local delivery of rGM-CSF.